Theclini butterflies from Weixi, China, with description of two new species (Lepidoptera: Lycaenidae) - Zhuang, Hailing; Yago, Masaya; Wang, Min (Zootaxa, 2015)
Thirteen species belonging to nine genera of the tribe Theclini are recorded from Weixi county, Yunnan province, China. Among which Noseozephyrus Koiwaya and Shirozuozephyrus kirbariensis machimurai Koiwaya are reported as a new record genus and a new record species for China, respectively, and two new species, Noseozephyrus lisus sp. n. and Shirozuozephyrus fibonacci sp. n., are described. All the species and their male genitalia are illustrated. A key for the genus of Shirozuozephyrus is provided.